1996
DOI: 10.1021/js950415w
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Transdermal Delivery of Fentanyl: Characterizations of Pressure-Sensitive Adhesives for Matrix Patch Design

Abstract: Transdermal delivery of fentanyl from various adhesive matrix formulations to achieve a steady-state skin flux was investigated. For this purpose, various pressure-sensitive adhesives selected from the three chemical classes of polymers (polyisobutylene (PIB), acrylate, and silicone adhesives) were characterized with respect to fentanyl's solubility, diffusion coefficient, and permeability coefficient. The solubility of fentanyl in various pressure-sensitive adhesives at 32 degrees C was determined by the drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 8 publications
3
34
0
1
Order By: Relevance
“…The lowest diffusion coefficient was observed for the rubberbased matrix. The order of silicone4acrylate4rubber was also reported by Roy et al (1996) for the diffusion of fentanyl. Paeonol diffusion measured in porcine stratum corneum was much lower than in the adhesives with a coefficient of 2.85 Â 10 À16 m 2 /s.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The lowest diffusion coefficient was observed for the rubberbased matrix. The order of silicone4acrylate4rubber was also reported by Roy et al (1996) for the diffusion of fentanyl. Paeonol diffusion measured in porcine stratum corneum was much lower than in the adhesives with a coefficient of 2.85 Â 10 À16 m 2 /s.…”
Section: Discussionsupporting
confidence: 65%
“…Already published data by Cantor (1999) and Roy et al (1996) were in the same order of magnitude (Table 1). The diffusion coefficient in the silicone adhesive BIO-PSA 7-4202 of Paeonol was the highest followed by the diffusion coefficient in the acrylic adhesive.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This work helped draw drug potency into the transdermal delivery picture. During this period, Gordon had a short stint at Cygnus and contributed to a key paper comparing suitable adhesive patches for the transdermal delivery of fentanyl [64]. This carefully conducted study showed that optimal and prolonged fentanyl human skin fluxes from different transdermal patches could be reached on attainment of maximum thermodynamic activity (fig.…”
Section: Gordon Flynn - Experimental Verification and Development Of mentioning
confidence: 99%
“…10 Human skin flux of fentanyl from poly-isobutylene (PIB) transdermal adhesive matrices at 32°C for a range of fentanyl loadings [64]. …”
Section: Gordon Flynn - Experimental Verification and Development Of mentioning
confidence: 99%